Exploring Phytochemical Profile, Pharmaceutical Activities, and Medicinal and Nutritional Value of Wild Edible Plants in Ethiopia - Woinshet Kassie Alemu; Limenew Abate Worku; Rakesh Kumar Bachheti; Archana Bachheti; Adam Mekonnen Engida (International Journal of Food Science)
In many parts of the world, wild edible plants (WEPs) constitute an essential component of the global food basket, providing an alternative source of wholesome and nourishing food. Ethiopia is one of countries of the world having largest concentrations of WEPs. In the country, various parts of WEPs, such as fruits, stems, leaves, tubers, roots, or entire plant sections, are frequently consumed and used as food sources for famine relief during seasonal food shortages, as well as for commercial purposes. WEPs have been also used in the country as sources of phytochemicals, traditional medicine, and pharmaceutical applications. Approximately 30%–40% of WEPs and over 413 different kinds of WEPs are commonly consumed by Ethiopians regularly. Most plant families utilized as WEPs are Moraceae, Fabaceae, Flacourtiaceae, Myrtaceae, Rosaceae, and Tiliaceae. The most widely used plant parts of WEPs were fruits. WEPs can be used as substitutes for traditional plant-based human diets because of their high nutritional value, which includes proteins, vitamins B2 and C, and low moisture content. This review focuses on using edible wild plants for pharmacological purposes, dietary supplements, and alternative medicine. Many obstacles prevent people from consuming WEPs, even when they are easily accessible and available. The use of WEPs must be encouraged by nutrition policies as one of the pillars of food and nutrition security. To increase yield, diversify the revenue streams of small-scale farmers, and protect the diminishing wild edible fruit resources, it is imperative to domesticate and enhance WEPs.